Dynamics of Dissemination and Outer Surface Protein Expression of Different European Borrelia burgdorferi Sensu Lato Strains in Artificially Infected Ixodes ricinus Nymphs - Fingerle, Volker (American Society for Microbiology, 2002)
Unfed Ixodes ricinus nymphs were infected with eight different strains and clones of Borrelia afzelii and B. garinii by capillary feeding. Except one B. afzelii clone, all expressed OspC in culture. Tick midguts and salivary glands were investigated at different time intervals for the presence of borreliae and for OspA and OspC phenotypes by immunofluorescence with simultaneous staining of OspA and OspC with monoclonal antibodies. Both species were transmittable to I. ricinus. All OspC-expressing strains and clones were able to disseminate into the salivary glands. In contrast, the OspC-negative B. afzelii clone was not detectable in the salivary glands, an indication that OspC plays an important role in dissemination. OspA-positive borreliae prevailed in the midgut. OspC positives were more frequent in the salivary glands than in the midgut. Notably, simultaneously OspA- and OspC-negative borreliae were detected in both organs. Kinetics of dissemination varied with the strains. The OspC-positive B. afzelii clone and all B. garinii OspA type 4 strains were detectable in the salivary glands right after feeding, while one B. garinii OspA type 6 strain invaded the salivary glands with a delay of 24 h. These findings support the hypothesis that OspA is abundantly expressed in unfed ticks while upregulation of OspC is also a prerequisite for dissemination in the vector for the Eurasian species B. afzelii and B. garinii. However, we found strain-specific dynamics of Osp expression and strain-specific kinetics of systemic infection in the vector tick and it appears that additional factors are involved in the initiation and regulation of the dissemination process.